Choriocarcinoma complicated with intra-abdominal and intrapleural hemorrhage in pregnancy – case report - Jaz, Kamila; Miedziarek, Cezary; Piasek, Ewa; Florek, Artur; Nowak-Markwitz, Ewa; Zaborowski, Mikołaj Piotr (Frontiers in Oncology, 2023)
Background: Choriocarcinoma is a rare neoplasm, exceptionally uncommon during an ongoing pregnancy. The disease often has a metastatic character, causing severe symptoms from various anatomic sites like the lungs, central nervous system, vagina, pelvis, or liver. Due to the condition's rarity, evidence on how to treat the choriocarcinoma originating during pregnancy remains scarce. Case presentation: Here, we present a case of a patient who developed choriocarcinoma before the 29th week of gestation. The neoplasm had a metastatic character, resulting in hemorrhage complicated by a hypovolemic shock. The patient underwent an emergency cesarean section and several surgeries to stop the massive hemorrhage. The treatment of the choriocarcinoma included chemotherapy with methotrexate followed by an EMA-CO regimen. The patient had a complete response to the therapy. The neonate suffered from complications related to prematurity. Conclusions: Metastatic choriocarcinoma can be a diagnostic and therapeutic challenge during ongoing pregnancy. Treatment of the disease can be associated with severe complications, but a complete response to chemotherapy is possible with a favorable long-term prognosis.